The diagnostic and predictive value of LncRNA PANDAR in gastric cancer and its regulation of gastric cancer progression via miR-637 - Weikang Su; Zhiling Zhong; Huazhi Li; Lingjia Meng; Xinqiang Zhong (Hereditas)
Abstract Background Gastric cancer (GC) remains a global health challenge due to its high morbidity, late-stage diagnosis, and limited therapeutic options. long non-coding RNA PANDAR has been implicated in tumorigenesis across multiple cancers, yet its role in GC pathogenesis and diagnostic utility is still unclear. The purpose of this study is to elucidate the diagnostic value of serum PANDAR and its regulatory mechanisms in GC progression. Methods lncRNA PANDAR levels were quantified in serum from 112 GC patients and 98 benign controls using RT-qPCR. The diagnostic value of lncRNA PANDAR was analyzed by ROC curve. Functional experiments (CCK-8, Transwell assays) and dual-luciferase reporter assays were conducted in HGC-27 and BGC-823 cells to explore the function of PANDAR in cell proliferation, migration, and invasion. The interaction between PANDAR and miR-637 was validated via bioinformatics prediction and co-inhibition assay. Results Serum PANDAR was significantly upregulated in GC patients (P < 0.0001) and exhibited high diagnostic accuracy (AUC = 0.913). Elevated PANDAR associated with advanced TNM stage (P = 0.047), lymph node metastasis (P = 0.023), and digestive system history (P = 0.035). PANDAR knockdown suppressed GC cell proliferation, migration, and invasion, effects reversed by co-inhibition of miR-637. Conclusions lncRNA PANDAR is a promising non-invasive diagnostic indicator of GC, and may serve as a biomarker for GC diagnosis and therapy. lncRNA PANDAR regulates the progression of GC through sponge miR-637.